Niveles de fertilización nitrogenada y población de insectos plagas en el cultivo de maíz (Zea mays L) en la zona de Montalvo - Morejón Camacho, Carlos Luis (2020)
Maize (Zea mays L.) is a traditional crop of great economic importance in Ecuador, considered as one of the main raw materials for the industry; since a number of by-products are produced from it for human and animal nutrition. This productive chain represents about 24% of the agricultural GDP (Gross Domestic Product) and it is estimated that around 80 thousand families that live in the coastal region are involved in the production of hard yellow corn. The objective of this research was to determine the incidence of insect pests based on different levels of nitrogen fertilization, it was carried out in the Los Ríos province, Montalvo canton, "La Maravilla" Campus. The treatments used in the experimental work were 5 levels of nitrogen fertilization, the experimental plots have a planting distance of 0.80 x 0.20, with an area per plot of 5m x 5m = 20m2, the treatments were distributed in a design of complete random blocks with 4 repetitions, to determine the difference between treatments, the Tukey test was used at 95% probability. During the crop cycle, the following were evaluated: days to flowering, plant height, evaluation of the insect pest population, grain-tuff ratio, yield per hectare and economic analysis. The results established that the economic evaluation made to the treatments with the application of 140kgN / ha, found the highest utility with $ 1192.7, having the lowest income with 120kgN / ha, with $ 1074.76.